Quality Of Work Life dan Komitmen Organisasi Terhadap Peningkatan Motivasi Kerja PNS: Studi Kausal Pada Pegawai Kantor Kecamatan Cakung Kota Administratif Jakarta Timur - Riskarini, Dian (Jurnal Manajemen, 2018)
This study was conducted to determine whether the Quality of Work Life and Organizational Commitment significant impact either partially or simultaneously to Work Motivation employee District Office Cakung East Jakarta Administration City. The population in this study were employees of the Office of Cakung Sub-district with a total sample of 66 employees. Using quantitative research by analyzing primary data questionnaire respondents parametric statistics to determine the effect partially or simultaneously from the independent variables on the dependent. The study states that there is significant influence and a positive correlation and direction of variables Quality of Work Life and Commitment Work partially or simultaneously to increase motivation Employee Work, although still weak, so it can be input for the organization to further improve aspects-aspects Quality of Work Life employee and his organization’s commitment to working motivation of employees in the organization can be better.